INCOME ANALYSIS OF WATER SWEETENER FARMING IN PENKASE - OELETA VILLAGE, ALAK DISTRICT, KUPANG CITY (CASE STUDY OF EL LABORA FARMING GROUP) - Matelda Febiati Olivia Ello; Santhy Chamdra; Bayu Mahendra (Undana Press, 2026)
This research has been conducted at the El Labora Farmers Group in Penkase - Oeleta Village, Alak District, Kupang City from April 2025 until completion. The purpose of this study was to determine the income of kale farming in the El Labora Farmers Group in Penkase - Oeleta Village, Alak District, Kupang City to find out the feasibility of kale farming in the El Labora Farmers Group in Penkase - Oeleta Village. The research location is Penkase - Oeleta Village, Alak District, Kupang City, which was done intentionally because the location is one of the centers of kale production. The determination of respondents in this study was carried out saturated, meaning that all members of the population were used as respondents. In this case, the population in question is kale farmers who are members of the El Labora Farmers Group in Penkase - Oeleta Village, Alak District, Kupang City, which totals 20 people. The results of the study showed that the average income of kale farmers was Rp. 221. 771 per month. The feasibility of water spinach farming in the El Labora Farmers Group in Penkase-Oeleta Village is indicated by the R/C ratio of 1.80. This value means that every Rp1.00 spent can generate revenue of Rp1.80. Thus, water spinach farming is declared feasible because it provides benefits to farmers.